BASIC INTRACELLULAR MECHANISMS OF FORMATION OF MORPHOLOGICAL CHANGES OF INTERNAL ORGANS IN FLUOROSIS (LITERATURE REVIEW) - Мария Сергеевна Бугаева; Олег Иванович Бондарев (Медицина в Кузбассе)
Chronic intoxication with fluoride compounds remains a serious public health problem, despite the decrease in their concentration in production and the common incidence level in recent years. Long-term exposure to the trace element and its ability to accumulate in the body are crucial factors in the morphogenesis of structural alterations. Since the main manifestation of fluorosis is damage to the teeth and skeleton, researchers traditionally focus their attention on studying mainly the pathology of these tissues. At the same time, in recent years, a large number of scientific papers devoted to the effect of fluoride on non-skeletal organs has accumulated.